Responses to exclusion are moderated by its perceived fairness. (7th October 2015) - Tuscherer, Taylor; Sacco, Donald F.; Wirth, James H.; Claypool, Heather M.; Hugenberg, Kurt; Wesselmann, Eric D.
Abstract: Experimental exclusion manipulations may induce exclusion in a way that participants perceive as unfair. Groups often use exclusion punitively to correct inappropriate behavior, however, which may lead to perceptions that it is potentially justified or fair. The current studies examined if individuals' perceptions of fairness with respect to an exclusion experience moderated their reactions. Participants wrote about or imagined a time in which they were excluded after they did something wrong (fair exclusion) or excluded even though they did nothing wrong (unfair exclusion) or about a mundane experience unrelated to exclusion (control). Compared with fair exclusion, unfair exclusion resulted in significantly weaker efficacy needs satisfaction (Studies 1, 2, and 4), greater antisocial intent (Study 3), and greater sensitivity to signs of interpersonal acceptance and rejection in a visual search task (Study 4). These results suggest that it is important to consider the role of perceived fairness in shaping responses to exclusion.